The Effect of Turnover Media on Increasing Knowledge of Compliance in Consumption of FE Tablets in Pregnant Women with Anemia - Reni Nurdianti; Ai Rahmawati; Lina Marlina; Mia Rumiati (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Anemia in pregnant women is a health problem that still exists throughout the world and has a negative impact on both mother and baby. The success of the government's Fe tablet administration program to treat anemia is strongly influenced by the adherence of pregnant women to consuming Fe tablets, besides that it is also influenced by the knowledge of pregnant women about anemia. Providing education to pregnant women is needed to increase knowledge of adherence to consumption of Fe tablets. Research Objectives: to determine the effect of flipchart media on increasing knowledge of consumption of Fe tablets in anemic pregnant women at the Cigeureung Health Center. The method used is quantitative with a pre-experimental approach. The sample used was 32 respondents from a population of 215 anemic pregnant women, the sampling technique used was purposive sampling. The instrument used was a questionnaire on increasing knowledge of consumption of Fe tablets that had been tested for validity and flipchart media. The data analysis used is the Wilcoxon test. Research results showed that there was an effect of flipchart media on increasing knowledge of adherence to consumption of Fe tablets with a p-value of 0.000 (p <0.05). The knowledge of pregnant women before being given education is sufficient then after being given education it is good. There is an effect of flipchart media on increasing knowledge of adherence to consumption of Fe tablets in anemic pregnant women at the Cigeureung Health Center. It is hoped that after learning about adherence to consuming Fe tablets, pregnant women with anemia can consume Fe tablets regularly.